Valahii (și nu numai ei), în Bucovina anilor 1788-1789: Wallachians (not solely them) in Bukovina during the years 1788-1789 - Diaconu, Mircea A. (Swedish Journal of Romanian Studies, 2023)
Who is Balthasar Hacquet (1739-1815)? A universal man and Enlightenment figure, Balthasar Hacquet was a physician, surgeon, geologist, mineralogist, botanist, fascinated by plants and animals, chemist, karstologist, palaeontologist, as well as ethnographer, ethnologist and anthropologist. The present study is prompted by the fact that between 1788 and 1789, Hacquet travelled through Bukovina, recently occupied by the Austrians, recording facts and giving testimonies on locals and settlers alike. The first part of the study analyzes the way Hacquet is published and received in Romania, between 1895 and 2007, from G. Bogdan-Duică (1895) to Nicolae Iorga, Leca Morariu, Radu Grigorovici, Leonte Ivanov. With insignificant exceptions, the most common opinion among Romanians is that Hacquet is unfair to the locals, conveying an unfavourable image of the Romanian-speaking population. Considering such an assessment inadequate, the author proposes in the second part of the study a re-reading of Hacquet's travel notes from an imagological perspective. The proposed analysis does not aim at reprimanding Hacquet for his views, nor at correcting them. Instead it aims at problematizing his perspective as the consequence of all sorts of contexts. Consequently, the ideas conveyed by Hacquet take on complex meanings that go beyond the limits of a divide between cultures. Finally, through the rereading it proposes, the study responds to its main objective, which is to dive into Hacquet's writing in order to reconstruct multiple aspects of life in Bukovina between 1788 and 1789.